2016
DOI: 10.1038/srep30347
|View full text |Cite
|
Sign up to set email alerts
|

M2 tumour-associated macrophages contribute to tumour progression via legumain remodelling the extracellular matrix in diffuse large B cell lymphoma

Abstract: Effects of M2 tumour-associated macrophages on the pathogenesis of diffuse large B cell lymphoma (DLBCL) are still controversial. Our data showed that the number of CD163-positive M2 macrophages correlated negatively with DLBCL prognosis. Macrophage depletion by clodronate liposomes significantly suppressed tumour growth in a xenograft mouse model of DLBCL using OCI-Ly3 cells. Moreover, M2 polarization of macrophages induced legumain expression in U937 cells. Exogenous legumain promoted degradation of fibronec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(83 citation statements)
references
References 32 publications
3
79
1
Order By: Relevance
“…Additionally, although TAMs have been associated with immunomodulation in other tumor types, their functional role has not yet been fully defined within the lymphoma microenvironment. In DLBCL, TAMs were defined in the TME as CD68 pos or CD68 pos CD163 pos and their prognostic impact remains controversial [15,55,56]. In particular, differing correlations with clinical outcome were observed and appeared to depend on the way TAMs were defined (i.e., as CD68 pos , CD163 pos , or CD68 pos CD163 pos ) and whether treatments included the anti-CD20 antibody Rituximab or not [57].…”
Section: In Germinal Center B-cell Lymphomas Myeloid Regulatory Cellmentioning
confidence: 99%
“…Additionally, although TAMs have been associated with immunomodulation in other tumor types, their functional role has not yet been fully defined within the lymphoma microenvironment. In DLBCL, TAMs were defined in the TME as CD68 pos or CD68 pos CD163 pos and their prognostic impact remains controversial [15,55,56]. In particular, differing correlations with clinical outcome were observed and appeared to depend on the way TAMs were defined (i.e., as CD68 pos , CD163 pos , or CD68 pos CD163 pos ) and whether treatments included the anti-CD20 antibody Rituximab or not [57].…”
Section: In Germinal Center B-cell Lymphomas Myeloid Regulatory Cellmentioning
confidence: 99%
“…26 The data on pathogenic and prognostic effects of M2 macrophages in nodal DLBCL are controversial. [27][28][29] Nevertheless, Shen et al 30 demonstrated that the number of M2 macrophages correlated negatively with prognosis in nodal DLBCL.…”
mentioning
confidence: 99%
“…The different localization patterns of legumain in and around tumor cells suggest site‐specific functions. Shen et al . reported that tumor‐associated M2 macrophages induced extracellular matrix degradation and the stimulation of angiogenesis by overexpressing legumain, thus promoting the progression of diffuse large B‐cell lymphoma.…”
Section: Discussionmentioning
confidence: 99%